Direito à saúde na constituição federal de 1988 e seus desdobramentos políticos e judiciais: o caso do combate à aids - Bueno, Luiz Roberto Ribeiro (2008)
This dissertation deals with the right to health. It is pointed out that this right nowadays belongs, due to the Constitution of the Federative Republic of Brasil, no longer to the field of natural law, but, precisely, to the field of positive law. The theory of positive law, therefore, gives its support, exclusively, to found the doctrinal conception here expounded. The first purpose is to emphasize that the right to health is a typical human right or, as expressed in the Brazilian Constitution, a fundamental right, since it grows out of the dignity of human being and it is intimately jointed to the basic human right, the right to life. Thus, the second topic to be treated refers to the dignity of human being as one of the constitutional fundamentals of the Law Democratic State, wise chosen by the Fundamental Law to designate the Country. It follows that the insertion of the right to health in the Constitution - it became a constitutional positive right - as a fundamental right it would be a mere consequence of this fundamentals. An analysis of the constitutional order is made, which conveys the conclusion that Brazil is projected to be a Social State, whose construction, however, is still in development. The following matter, consequently, is a study of the characteristics of the Welfare State. The next step analyses two hindrances to the full effectiveness of the right to health: the economic power of the pharmaceutical industries and the inertia or omission of the Government. Finally, it is studied the government public policies as to public health, the jurisprudence of the Brazilian Supreme Court (Supremo Tribunal Federal) and the World Health Organization position about fight against the HIV, specially examining ethical questions.